Dry deposition of dirt on building surface fouling - Muhammad Junaidi Arip (2016)
Dirt particles, pollutants or dusts often has its ways to get embedded onto a surface of a material, typically materials with rough surfaces. This undesired accumulation of dirt such as on building surfaces not only affects its aesthetic image but more importantly could result in the reduction of reflectance which ultimately leads to an increased in energy consumption. Deposition of dirt particles on various cool roof coating coupons were investigated. Typically, particle capture for rougher surface shows a higher particle buildup than those with a smoother surface. Effects on climate changes such as precipitations and pollutants were also investigated as these factors might affect the total amount of dirt accumulated. Methods of collecting dirt particles by means of surrogate surfaces were designed to establish feasible results for the particles collected. Surface temperature of aged coupons were compared with newly coated ones which suggest lower reflectance value for the aged ones. Based on the reflectance value, the energy consumption were estimated.